Application of low-energy X-rays to stimulate moss applied in environmental monitoring - Nguyễn, Thị Minh Sang (2024)
Low-dose radiation stimulates plant growth, particularly in mosses, thereby enhancing their ability to absorb airborne elements using the moss bag technique. An experiment was conducted to investigate the effects of low-energy X-ray radiation (1-20 Gy, with a 1 Gy interval) on the growth of Babular indica moss. The results revealed that doses ranging from 2 Gy to 16 Gy improved moss growth compared to the non-irradiated control. The optimum stimulatory effect was observed at 14 Gy, as indicated by morphological characteristics, moss weight, and chlorophyll content. Consequently, 14 Gy was selected as the irradiation dose for moss in the monitoring environment. Analysis of element concentrations using Total Reflection X-ray Fluorescence (TXRF) demonstrated that the irradiated moss exhibited significantly improved element absorption compared to the non-irradiated moss, although still lower than that of natural moss. This study emphasizes that low-dose (14 Gy) radiation treatment of mosses holds promise as a solution for achieving more accurate results and a closer reflection of real air conditions in environmental monitoring using the moss bag technique.